Advances in sugarcane biorefinery : technologies, commercialization, policy issues and paradigm shift for bioethanol and by-products - Chandel, Anuj Kumar; Silveira, Marcos Henrique Luciano (Elsevier, 2017)
Advances in Sugarcane Biorefinery: Technologies, Commercialization, Policy Issues and Paradigm Shift for Bioethanol and By-Products, by Chandel and Silveira, compiles the basic and applied information covering cane and biomass processing for sugar and ethanol production, as well as by-products utilization for improving the economy of sugarcane biorefineries. In this unique collection of 14 chapters, specialists in their field provide critical insights into several topics, review the current research, and discuss future progress in this research area. The book presents the most current advances in sugarcane biorefinery, including sugarcane crop cultivation, new sugarcane varieties, soil health, mechanization of crop, technical aspects of first and second generation ethanol production, economic analysis, life cycle assessment, biomass logistics and storage, co-generation of heat and electricity, process intensification and alternative by-products utilization. The book also explores the business ecosystem of sugarcane biorefineries, marketing analysis of ethanol demand and price dwindling patterns, aiming for a futuristic scenario. This book will be especially useful for scientists, researchers and technicians who are working in the area of biomass based biorefineries, as well as professionals in the sugar and alcohol industry. It also brings relevant content for policy makers, market analysts, agriculture scientists and managers.